2021
DOI: 10.1002/advs.202102157
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Impairs Embryonic Myogenesis by Enhancing BMP Signaling within the Dermomyotome

Abstract: Obesity during pregnancy leads to adverse health outcomes in offspring. However, the initial effects of maternal obesity (MO) on embryonic organogenesis have yet to be thoroughly examined. Using unbiased single-cell transcriptomic analyses (scRNA-seq), the effects of MO on the myogenic process is investigated in embryonic day 9.5 (E9.5) mouse embryos. The results suggest that MO induces systematic hypoxia, which is correlated with enhanced BMP signaling and impairs skeletal muscle differentiation within the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Peritoneal immune cells from three mice of each group were isolated and collected from the peritoneal fluid following our established method 5 . After removing red blood cells by lysis, remaining cell mixtures were used for cDNA library constructions following the manufacturer’s protocol (10X Genomics, Inc.) of the Chromium Single Cell 3' Library & Gel Bead Kit V3 76 . All samples were multiplexed together and sequenced across one single lane of an Illumina NovaSeq 6000 S4.…”
Section: Methodsmentioning
confidence: 99%
“…Peritoneal immune cells from three mice of each group were isolated and collected from the peritoneal fluid following our established method 5 . After removing red blood cells by lysis, remaining cell mixtures were used for cDNA library constructions following the manufacturer’s protocol (10X Genomics, Inc.) of the Chromium Single Cell 3' Library & Gel Bead Kit V3 76 . All samples were multiplexed together and sequenced across one single lane of an Illumina NovaSeq 6000 S4.…”
Section: Methodsmentioning
confidence: 99%
“…Peritoneal immune cells were isolated and collected from the peritoneal fluid following our established method (Shi et al, 2021). After removing red blood cells by lysis, remaining cell mixtures were used for cDNA library constructions following the manufacturer’s protocol (10X Genomics, Inc.) of the Chromium Single Cell 3’ Library & Gel Bead Kit V3 (Zhao et al, 2021). All samples were multiplexed together and sequenced across one single lane of an Illumina NovaSeq 6000 S4.…”
Section: Methodsmentioning
confidence: 99%
“…This is partially caused by the very small sizes and immaturity of early embryos. Using advanced techniques of single-cell RNA sequencing, we have identified and characterized myogenic precursors at various differentiating stages within the DM of mice at E9.5, the initial stage for organogenesis [ 72 ]. We found that maternal obesity-induced systemic hypoxia enhanced BMP signaling transduction within the DM, which suppressed the expression of Mef2c , a critical transcription factor for myofiber differentiation and metabolism.…”
Section: Developmental Programming At the Embryonic Stagementioning
confidence: 99%